Evaluación del control de tráfico para los servicios de cibercafés utilizando tecnología mikrotik - Lopez Villena, Jefferson Adrian (2021)
The purpose of this case study is to evaluate the traffic control for the cybercafe "Feffrapycopy" in which certain anomalies regarding the security and mismanagement of the network could be evidenced, so it is intended to use MikroTik technology in order to better manage network resources and thus avoid traffic and network saturation in order to provide good service to customers. Nowadays there is a great tendency in the automated world due to the fact that all kind of information is redirected through the communication highway known as the Internet, which has made conflicts in the central networks thanks to the great proportion of data that the routers and switches handle. and transitions; even the other way around once we talk about using the existing resources. Computer networks have become correct, both for individuals and organizations, because through these networks we are able to communicate with each other for business purposes, something personal and even in case of an emergency. The administration of the information systems belongs to the essential resources for the relationship and the advance of the information technologies. After having concluded the case study with the respective analysis of the information collected both by the methodologies implemented and the research instrument that allowed to identify current problems such as wifi slowdown, slowness and collapse when browsing websites all this produced by network traffic that generates saturation to poor management of bandwidth. The basic concepts related to traffic control were studied and the use of simple queuing techniques to configure the bandwidth of the equipment was analyzed.